The relationship between mental workload and general health among welders of Tehran Heavy Structure Metal Company - Zare, Sajad; Hasheminejad, Naser; Dehesh, Tania; Hasanvand, Davood; Kazemi, Reza; Ahmadi, Saeid (Archives of Advances in Biosciences, 2016)
Mental workload is one of the factors that influence individuals’ performance in the work environment as well as their efficiency and productivity. The present study aimed at examining the association between mental workload and general health among welders of Tehran Heavy Structuress Metal Company.This cross-sectional study was conducted in 2016. The sample included 100 welders who were working in Tehran Heavy Structures Metal Company. Sampling was done through conducting a census. A demographic questionnaire, General Health Questionnaire-28 (GHQ-28), and National Aeronautics and Space Administration Task Load Index (NASA-TLX) mental workload questionnaire were used to collect data. The obtained data were fed into SPSS (version 22) and analyzed through Chi-square, one-way ANOVA, Kruscal Wallis Test, Pearson product moment correlation, and Mann-Whitney U Test.The results showed that the participating welders had an average age of 36.16±7.81, an average work experience of 9.65±5.83, and a BMI of 25.95±3.39 kg/m2. The mean and standard deviation of the overall score of welders’ mental workload were 65.88±21.15. The cut-off scores for the total mental workload questionnaire and the subscales were respectively set at 23 and 6. The results demonstrated that 26% of the welders were suspected of mental disorder. Furthermore, the results of Pearson correlation indicated that there was no significant relationship between the overall score of NASA mental workload and that of general health (p-value>0.05).Welders’ mental workload is relatively high. Therefore, further research should be conducted in order to identify main risk factors that lead to mental and health disorder. Future studies should also be performed to present some solutions for te purpose of decreasing or preventing these side effects among welders as much as possible.